The Stability of Gold Nanoparticles-Prussian Blue Based Sensors for Biosensor Applications in Clinical Diagnosis - Phonklam, Kewarin; Thongkhao, Piromya; Phairatana, Tonghathai (Journal of Health Science and Medical Research, 2023)
Objective: Many medical biosensors have been widely developed for use in clinical diagnosis as point-of-care testing. However, most of them still suffer from inaccurate results, caused by the lack of biosensor stability under variable pH of biofluid samples; such as urine. Hence, the instability of pH variations is one of the key challenges for electrochemical biosensors. In this study, the development of gold nanoparticles-Prussian blue (AuNPs-PB) based screen-printed electrodes were investigated for their performance, in terms of electrochemical stability within various pH solutions. Material and Methods: The AuNPs-PB modified screen-printed gold electrode (SPAuE) was developed and optimized using an electrode-position technique and cyclic voltammetry, respectively. As compared to PB modified SPAuE, the signal response of cyclic voltammograms at AuNPs-PB modified SPAuE was examined in a phosphate buffer solution with different pH values. The electrochemical stability of the modified SPAuE was considered on the invariability of the PB redox current in different pH solutions. Results: The result revealed that stable current signals of PB in different pH solutions of the AuNPs-PB modified SPAuE showed good electrochemical stability, with a relative standard deviation (RSD) of oxidation and reduction peak currents being 1.0% and 1.1%, respectively. The signal stability results exhibited over two and five times when compared to those of the PB modified SPAuE (without gold nanoparticles), which were 2.4% and 5.6% RSD, respectively. Conclusion: The AuNPs-PB modified SPAuE provides a potentially alternative tool for the enhancement of electrochemical stability for use in medical biosensor applications.